The Impact of milkfish industry cluster program on the Department of Trade and Industry in Region 1 - Rivera, Ma. Cynthia G. (DMMMSU-OUS : [s.n.], 2016)
Region I was piloted as one of the NICCEP regions and identified and supported the bangus (Milkfish) industry cluster in 2010. Milkfish being the primary region product focus of the One Town One Product (OTUP) and regional industry focus under the industry cluster program ushered in a convergence of assistance from the ICA Local Government Units, other Government Agencies, the Academe, private groups and the Department of Trade and Industry. The rolling out of the Industry Cluster Program in the region enabled the identified milkfish stakeholders to craft Roadmaps for Action for the identified sectors of the region. This study determined the impact of the Milkfish Industry Chester Program in Region I after a five year period. The study analyzed and interpreted data gathered from the milkfish growers, processors and traders from the province of Pangasinan and La Union. Likewise, a case study among non-project beneficiaries was conducted in Ilocos Sur to compare and contrast project among beneficiaries and non-beneficiaries. Majority of the milkfish processor in Pangasinan availed of the NICCEP Fed capacity trainings help improve their production efficiency and product quality. The milkfish growers, processors and traders generally improved their economic performance on terms of safe production volume, jobs created investments generated and mark developed in 2015 compared to their station when the milkfish industry cluster program we implemented in 2010. On the other hand, non-project beneficiaries, though they have grown on terms of sales, production, volume jobs, investment and market compared to their situation in 2010 marginal compared to the growth achieved by the project beneficiaries.
Bibliography: pages 99-103.
DMMMSU-OUS Library
Keywords: Fishery industry